Investigation of Inversion Charge Characteristics and Inversion Charge Loss for InGaAs Negative-Capacitance Double-Gate FinFETs Considering Quantum Capacitance - Shih-En Huang (IEEE Journal of the Electron Devices Society, 2020)
This paper investigates the inversion charge characteristics and quantum-capacitance induced inversion charge loss for In0.53Ga0.47As negative-capacitance FinFETs (NC-FinFETs) using theoretical calculation corroborated with numerical simulation. Our study indicates that, the boost of inversion charges due to negative capacitance increases with increasing remnant polarization Pr. In addition, the inversion charge boosting for the In0.53Ga0.47As device is significantly larger than that of the Si (110) device due to the step-like inversion capacitance characteristic stemming from the 2D density-of-states of the In0.53Ga0.47As device. In other words, the quantum-capacitance induced inversion-charge loss for III-V channel can be mitigated in NCFETs.